A NATUREZA DOS SABERES DOCENTES FRENTE À PRÁTICA PEDAGÓGICA NA EDUCAÇÃO INFANTIL - Macenhan, Camila (2015)
This work has as object of study the pedagogical knowledge of Early Childhood Education teachers before their teaching practice. The research was developed from the qualitative approach (RICHARDSON et al., 2009), being the central question:What is the nature of the pedagogical knowledge of Early Childhood Education teacher before pedagogical practice? The research objectives were: a) reveal through inferential interpretations the nature of pedagogical knowledge of the Early Childhood Education teacher before pedagogical practice; b) discuss the pedagogical practice of the Early Childhood Education teacher and his/her relationship with pedagogical knowledge; c) highlight the influence of the professional development of the Early Childhood Education teacher in the constitution of pedagogical knowledge. Throughout the investigative process, we address the concept of field and habitus; the specificity of teaching (TARDIF; LESSARD, 2005);the issues about teacher education and professionalization (NÓVOA, 1991, 1992);the typologies of pedagogical knowledge (TARDIF, 2002; GAUTHIER, 2006;SHULMAN, 2005); the teachers’ education in the professional development perspective (MARCELO GARCIA, 1995, 2009; VAILLANT; CARLOS MARCELO, 2012) and pedagogical practice from a broader concept than the action (GIMENO SACRISTÁN, 1999). The research data were obtained by carrying out observations and semi-structured interviews, from Lüdke and André (1896) and Vianna’s (2003) point of view. The research involved four (4) Early Childhood Education teachers, two (2) of them work in municipal public schools of Ponta Grossa/PR and the other two (2) in private schools in the same city. We counted on the collaboration of three (3) educational institutions in the mentioned city, a Municipal Early Childhood Education Centre (called CMEI) and two Early Childhood Education Centers (called CEIs). We used the content analysis (BARDIN, 2011) for the analysis and data processing. As a result, we observed the fact that the teacher mobilizes in his/her practice different knowledge, which is not derived only on the initial and continuing education, although training courses are responsible for working the expertise of teaching. The results show that the pedagogical knowledge originates from both teacher education courses and their personal and professional experiences, so the pedagogical knowledge has such elements as sources of learning, they undergo development processes and are mobilized in pedagogical practice thereby they influence and receive interference from this practice. From the results, we highlight the importance of enhancing the performance and the permanent education of teachers from the perspective of teacher professional development so that it is possible to unveil essential points about the nature of teacher knowledge.